2011
DOI: 10.15208/beh.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between transformational leadership and employees’ satisfaction at Jordanian private hospitals

Abstract: The present study has aimed at identifying the relationship between transformational leadership and job satisfaction of registered nurses at Jordanian private hospitals, the population of the study consisted of registered nurses at private hospitals located in Amman (capital of Jordan). There have been 200 surveys mailed out to registered nurses. One hundred and sixty eight usable surveys have been returned with an 83% response rate. Regarding transformational leadership, the survey was adapted from the Multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…On the other hand, Morsiani et al (2017) found idealised influence (attributed) to have the highest positive correlation. These findings are conflicting, but all the dimensions seem to increase nurses' job satisfaction with Mohammad et al (2011) noting that they influence intrinsic job satisfaction more than extrinsic job satisfaction. Similar to the findings of S7, transformational leadership can, therefore, be used to promote satisfiers or motivators of job satisfaction postulated by Herzberg et al (2008).…”
Section: Relationship Between Transformational Leadership Style and Nmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, Morsiani et al (2017) found idealised influence (attributed) to have the highest positive correlation. These findings are conflicting, but all the dimensions seem to increase nurses' job satisfaction with Mohammad et al (2011) noting that they influence intrinsic job satisfaction more than extrinsic job satisfaction. Similar to the findings of S7, transformational leadership can, therefore, be used to promote satisfiers or motivators of job satisfaction postulated by Herzberg et al (2008).…”
Section: Relationship Between Transformational Leadership Style and Nmentioning
confidence: 94%
“…The dimension of transformational leadership associated with the strongest relationship with job satisfaction appears not to be clearly understood with S7 citing inspirational motivation as the strongest predictor, but other studies indicating differing results. According to Mohammad et al (2011), all the transformational leadership dimensions were correlated with job satisfaction of Jordanian private hospital nurses; however, the strongest correlation with job satisfaction (intrinsic and extrinsic) was found with intellectual stimulation. On the other hand, Morsiani et al (2017) found idealised influence (attributed) to have the highest positive correlation.…”
Section: Relationship Between Transformational Leadership Style and Nmentioning
confidence: 96%
“…Another link that has been widely explored is between transformational leadership and job satisfaction (Boamah et al, 2018). In a study of Pakistani bank staff (Fatima et al, 2011) and Jordanian nurses (Mohammad et al, 2011), the researchers found a positive link between this leadership style and job satisfaction. In a Malaysian school, Arokiasamy et al (2016) found similar results, where a significant association exists between the transformational leadership of headmasters and teachers' job satisfaction.…”
Section: (A) Transformational Leadershipmentioning
confidence: 99%
“…Earlier research of workplace spirituality also revealed the benefit of spirituality at work in enhancing human wellness; this is because the spiritual aspect does not only divert to the physical aspects but rather to the social and emotional concerns (Adawiyah et al , 2020; Carmody et al , 2008). The professional nursing future depends on discovering ways to form positive and high-grade workplace environments, which encourage meaning and wellness in life through mutual interconnectedness between individuals, relatives, community, society, nature and the significant or sacred (Mohammad et al , 2011).…”
Section: Introductionmentioning
confidence: 99%